2014
DOI: 10.32607/20758251-2014-6-1-96-101
|View full text |Cite
|
Sign up to set email alerts
|

Composite Scaffolds Containing Silk Fibroin, Gelatin, and Hydroxyapatite for Bone Tissue Regeneration and 3D Cell Culturing

Abstract: Three-dimensional (3D) silk fibroin scaffolds were modified with one of the major bone tissue derivatives (nano-hydroxyapatite) and/or a collagen derivative (gelatin). Adhesion and proliferation of mouse embryonic fibroblasts (MEF) within the scaffold were increased after modification with either nano-hydroxyapatite or gelatin. However, a significant increase in MEF adhesion and proliferation was observed when both additives were introduced into the scaffold. Such modified composite scaffolds provide a new and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
0
14
0
1
Order By: Relevance
“…The report demonstrated that silk fibroin scaffolds needed special modifications to enhance the biological performance to induce the formation of bone tissue . Therefore, modified silk fibroin scaffolds with decellularized pulp and fibronectin were presented in this research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The report demonstrated that silk fibroin scaffolds needed special modifications to enhance the biological performance to induce the formation of bone tissue . Therefore, modified silk fibroin scaffolds with decellularized pulp and fibronectin were presented in this research.…”
Section: Discussionmentioning
confidence: 97%
“…The report demonstrated that silk fibroin scaffolds needed special modifications to enhance the biological performance to induce the formation of bone tissue. 47 Therefore, modified silk fibroin scaffolds with decellularized pulp and fibronectin were presented in this research. The aim of modification is to mimic the microenvironment of decellularized pulp/fibronectin that can enhance the biological performance of silk fibroin scaffolds such as cell adhesion and proliferation.…”
Section: Biological Performance Of Modified Silk Fibroin Scaffoldsmentioning
confidence: 99%
“…Cell proliferation-related genes were identified at both time points in peri-implant bone healing. As previously mentioned, cell proliferation is a key biological process in tissue development and regeneration [ 36 , 37 ]. The present study identified several genes, such as CDK14 , PLCD1 , and ZBTB16 , which were upregulated during peri-implant bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Зарубежные компании придают большое значение усовершенствованию имеющихся материалов и созданию новых полимеров для возможной имплантации в организм человека, в связи возросшим спросом на данный вид продукции. В зависимости от области применения изготовляемых продуктов, помимо высоких биосовместимых свойств, пластики должны соответствовать другим немаловажным критериям [21]. Пластмассы, использующиеся для изготовления зубных имплантатов, ортопедических протезов, должны обладать достаточно прочностными качествами.…”
Section: D-биопринтерыunclassified